Relationship of Breast Volume and Breast Malignancy Risk Based on BI-RADS Classification Categories In Mammography - Yueniwati, Yuyun; Fahmi Fahanani, Agwin; Atsil Lathifa, Jauza (Jurnal Ilmu Kedokteran Keluarga, 2023)
Breast cancer is a major global public health problem and the most common type of cancer. The incidence of cases in Indonesia was about 42.1 per 100.000 population in 2019. Multiple risk factors underlie breast cancer malignancy. However, breast volume has not yet been included as a risk factor for breast cancer. This study aims to analyze the association between breast volume and breast malignancy. This cross-sectional study obtains breast volume and BI-RADS score by performing a mammography assessment at Dr. Saiful Anwar General Hospital, Malang. The inclusion criteria were women aged > 40 years and excluded those who have mammography contraindications such as pregnancy and breastfeeding. The parameters for calculating breast volume were the width, height, and compression thickness. The malignancy determination was use the BI-RADS category. There was no significant association using the Kruskal-Wallis test (p = 0.273, p > 0.05). The conclusion is there was no association between breast volume and the risk of malignancy based on BI-RADS mammography.